1989
DOI: 10.1210/endo-124-4-1717
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prolactin Synthesis in Vitro by Estrogenic and Antiestrogenic Derivatives of Estradiol and Estrone*

Abstract: The estrogenic and antiestrogenic activities of derivatives of estradiol and estrone were determined in vitro using the ability of primary cultures of immature rat pituitary cells to synthesize PRL. Estradiol derivatives were the most potent estrogens in the assay. Large ethinyl substitutions in the 17 alpha position generally caused a decrease in estrogenic potency (up to 1000-fold). The 3 phenolic hydroxyl was important, but not essential, for the estrogenic activity of the estradiol molecule. Estratriene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Concentrations of prolactin were greater in the follicular fluid of normal, nonatretic follicles compared with atretic follicles (Lebedeva et al, 1998). Estrogens stimulate synthesis of pituitary prolactin (Jordan and Koch, 1989), and follicular prolactin paralleled follicular estrogen after PGF 2α administration in beef heifers (Wise and Maurer, 1994). Concentrations of prolactin were influenced by BC and luteal status of cows in the current experiment.…”
Section: Resultsmentioning
confidence: 51%
“…Concentrations of prolactin were greater in the follicular fluid of normal, nonatretic follicles compared with atretic follicles (Lebedeva et al, 1998). Estrogens stimulate synthesis of pituitary prolactin (Jordan and Koch, 1989), and follicular prolactin paralleled follicular estrogen after PGF 2α administration in beef heifers (Wise and Maurer, 1994). Concentrations of prolactin were influenced by BC and luteal status of cows in the current experiment.…”
Section: Resultsmentioning
confidence: 51%
“…Studies examining estrogenicity have found that 17ß-estradiol is up to 10 times more potent than estriol [23]. The hydrogen bond interactions between amino acids within the estrogen receptor structure and the phenolic hydroxyl group present on 17ß-estradiol play a vital role in the function of the estrogen receptor [24], however the phenolic hydroxyl group can also confer antioxidant activity to 17ß-estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro reflect constant concentrations to create knowledge of intrinsic efficacy of the complex specifically. The modulation of the prolactin gene through rigorous SAR (Jordan et al , 1984, Jordan et al , 1986, Jordan, 1987, Jordan and Koch, 1989, Lieberman et al , 1983a, Lieberman et al , 1983b, Robinson et al , 1988, Tate et al , 1984b) created the “crocodile model” of antiestrogen action (Jordan, 1987) with the antiestrogenic side chain predicted to interact at an “antiestrogenic region” of the ligand-binding domain. The side chain prevented the “jaws” closing over the ligand thereby preventing activation of the ER complex (Jordan, 1984, Lieberman et al , 1983b, Tate et al , 1984a).…”
Section: A Molecular Model Of Estrogen/antiestrogen Actionmentioning
confidence: 99%